Ceftriaxone-induced Agranulocytosis - Lénio Couto; André Goulart; Ivone Valadão; Magda Garça; Maria Beatriz Santos; Pedro Cota; Carolina Teixeira (European Journal of Case Reports in Internal Medicine, 2021)
Ceftriaxone is a widely used antibiotic regarded as safe and effective. Drug-induced agranulocytosis is a life-threatening adverse reaction and few reports related to ceftriaxone were found in a review of the literature. The authors present a case of ceftriaxone-induced agranulocytosis, in which a brain abscess was diagnosed and ceftriaxone was commenced. Neutropenic fever occurred on the 29th day of therapy with a cumulative dose of 116 g ceftriaxone and a neutrophil nadir of 0.1×109/l. Ceftriaxone was withheld, filgrastim was administered for 3 days and neutrophil normalization was achieved. Although rare, ceftriaxone-induced agranulocytosis may occur in patients on a long course of ceftriaxone therapy. Prompt recognition and drug withdrawal are required.